2020
DOI: 10.3390/ijms21113930
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Dendritic Cell Subsets in Cancer Progression and Clinical Implications

Abstract: Dendritic cells (DCs) constitute a complex network of cell subsets with common functions but also with many divergent aspects. All dendritic cell subsets share the ability to prime T cell response and to undergo a complex trafficking program related to their stage of maturation and function. For these reasons, dendritic cells are implicated in a large variety of both protective and detrimental immune responses, including a crucial role in promoting anti-tumor responses. Although cDC1s are the most potent subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 209 publications
0
61
0
Order By: Relevance
“…The inhibition of DCs’ viability by TME is not restricted to the hypoxic microenvironment. Tumor-derived factors, such as VEGF-A, PGE2, and ATP, keep infiltrating DCs at an immature state that is not functional for the activation of T cell response [ 10 ]. Indeed, one of the characteristics of the TME is the accumulation of immature DCs that are not able to finally differentiate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of DCs’ viability by TME is not restricted to the hypoxic microenvironment. Tumor-derived factors, such as VEGF-A, PGE2, and ATP, keep infiltrating DCs at an immature state that is not functional for the activation of T cell response [ 10 ]. Indeed, one of the characteristics of the TME is the accumulation of immature DCs that are not able to finally differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, tumors impair DC biology in many ways, including the modulation of DC differentiation, and the modification of their metabolism by decreasing the availability of nutrients and oxygen, and, therefore, by compromising DC viability [ 3 ]. Previous reports have shown that DCs are affected by hypoxia in terms of cell survival, differentiation, activation, and migration [ 9 , 10 ]. In addition, we have previously demonstrated that a prolonged exposure to hypoxia resulted in a pro-apoptotic program in immature DCs, along with PI3K/AKT inhibition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prominent biological features of DCs that are associated with initiation of the adaptive immune response, DCs are no doubt an ideal vaccine target to prevent cancers. Moreover, DCs secrete various kinds of cytokines and chemokines, which are indispensable for T cell proliferation, activation, and recruitment [138,139]. Thus, numerous preclinical and clinical trials have been initiated in previous decades to assess DC-based mRNA vaccines.…”
Section: Dendritic-cell-based Mrna Vaccinesmentioning
confidence: 99%
“…The TME is home to several soluble factors that may promote a tolerogenic or immunosuppressive DC phenotype; these include IL-10, IL-6, VEGF, CSF-1, β-catenin, TGF-β and PGE2 [ 62 ]. VEGF [ 63 ], β-catenin [ 64 ] and PGE2 [ 65 , 66 ] production by tumour cells and IL-10 secretion by tumour-associated macrophages [ 67 ] have been shown to inhibit DC function and/or recruitment.…”
Section: Cell Typesmentioning
confidence: 99%